Neck circumference as a potential marker of metabolic syndrome among college students - Dayse Christina Rodrigues Pereira; Márcio Flávio Moura de Araújo; Roberto Wagner Júnior Freire de Freitas; Carla Regina de Souza Teixeira; Maria Lúcia Zanetti; Marta Maria Coelho Damasceno (Universidade de São Paulo, 2014)
OBJECTIVE: to relate neck circumference with metabolic syndrome and its criteria among college students.METHOD: cross-sectional study conducted with 702 college students in Fortaleza, CE, Brazil from September 2010 to June 2011. Socio-demographic data, waist circumference and neck circumference were collected together with blood pressure, fasting blood sugar, triglyceride levels, and HDL-C.RESULTS: 1.7% of the studied sample presented metabolic syndrome. Of these, 58.3% presented altered neck circumference (p<0.006). As neck circumference decreases, pressure levels improve (p<0.001). Additionally, college students with high fasting blood sugar (p=0.003) and high triglyceride levels (p<0.001) presented higher values of neck circumference.CONCLUSION: neck circumference is a potential predictive marker in the detection of metabolic syndrome and its components among college students.